Candidates for RR Lyrae in binary systems from the OGLE Galactic bulge survey - Prudil, Zdeněk; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society. Letters, 2019)
ABSTRACT. We present 20 newly discovered candidates for binary systems with an RR Lyrae companion. Using the photometric data from the Optical Gravitational Le
Gesehen am 01.07.2019